Static and Dynamic Properties of Clay Brick Materials - Chiu, Yu-Wen (Curtin University, 2021)
This study investigates and quantifies the static and dynamic mechanical properties of clay bricks. The compressive and tensile strengths, corresponding failure strains and Young’s modulus of the three different types of brick materials at different strain rates are experimentally quantified. Based on the test results, empirical relations of dynamic increase factor (DIFs) with respect to strain rate are derived for brick materials. Correlation between dynamic split-tensile strength and dynamic direct tensile strength is examined, and a conversion relationship is proposed.